Demand impact for prices ending with “9” and “0” in online and offline consumer goods retail trade channels - Lopez-Pastor, Marcial (2020)
Studies on demand impact for 9-ending and rounded prices have so far offered controversial results, with hardly any research focusing on their effect on online commerce or in a multichannel sales context. Our study aims to fill this gap by analyzing the conditions that influence the strategy behind setting such type of pricing in the multichannel retail business of fast-moving consumer goods (FMCG). To test the formulated hypotheses, scanner data from FMCG retailers are used. In addition to “demand” and “price”, “promotion communication”, “retailer type” and “price level” are included as moderators between 9-ending, rounded prices and demand. The results aim to provide, both in the academic and business fields, systematic findings of pricing relationships between online and offline channels which contribute to a better management strategy for “9-ending” and “rounded” prices.